A learning analytics approach to investigating pre-service teachers' change of concept of engagement in the flipped classroom. Issue 2 (4th February 2022) - Sun, Fu-Rong; Hu, Hong-Zhen; Wan, Rong-Gen; Fu, Xiao; Wu, Shu-Jing
ABSTRACT: To determine the impact of cognitive style on change of concept of engagement in the flipped classroom, a sequential analysis from the perspective of Bloom's Taxonomy was conducted to establish if significant differences existed between the learning achievements and engagement of students with different cognitive styles. The participants were pre-service teachers who had registered for a school-based curriculum development methodology course in China, with a total of 53 students from two classes, who performed a total of 1, 599 behaviors in the discussion sections. The results show that the concepts of "evaluate" (31.52%) and "analyze" (27.77%) were the two most frequent behaviors in the Bloom's Taxonomy. The "remember" and "evaluate" were the significant starting behaviors for all of the students; "remember" and "evaluate" were the significant starting behaviors for the intuitive-style students, while "understand" was a significant starting behavior for the analytical-style students. This confirms that the students with different cognitive styles implemented multiple strategies for learning. It is also found that the ﬂipped learning promoted the students' achievement. The conclusions suggest that it is important to match the cognitive styles of students as well as the instructional methods in order to improve students' learning.